Gazing Into the Future— Long term studies and scientific Crystal Balls - Lima, M. L. (IAPS Conference, 2020)
Long term studies are fundamental to assess the impact of environmental interventions. In fact, many important experimental studies give us information about immediate consequences of interventions, but only long term studies allow for the detection of late effects or even the fading out of the initial effects. However, in order to design long term studies, many early decisions have to be made in order to ensure that the right variables, the right samples and the right procedures will be in place – and for that the available science crystal balls not always help us. This presentation will be based on the challenges faced in almost 25 years study on the psychosocial impacts of a waste incinerator. The first study was conducted in 1995 and the last one in 2018, the 23th wave of data collection. The first survey study was conducted by face to face interview during the environmental impact assessment stage of the project, to inform the decision of building (or not) a waste incinerator. The decision to construct the incinerator required the regular monitorization of its psychosocial impacts. During the construction phase, one baseline and 4 assessment were conducted (2 two during summer and 2 during winter time). And after the construction, 12 more waves of face to face interviews and 5 of telephone surveys were conducted. Long term processes such as the adaptation to the threat and the normalization of the risks could be described, but our doubts persist on what were the impacts that were not foreseen.